2012
DOI: 10.1002/pds.3257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Centers for Medicare & Medicaid Services national coverage determination on erythropoiesis‐stimulating agent and transfusion use in chemotherapy‐treated cancer patients

Abstract: ESA use decreased sharply post-NCD. This was accompanied by an estimated 1.1% (95% confidence interval -0.8% to 3.0%) absolute increase in transfusion use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…If approved, CMS enters into a Data Use Agreement (DUA) with the researcher. These data have been used to describe patterns of morbidity2 and mortality3 and burden of disease,4,5 compare the effectiveness of pharmacologic therapies,6–9 examine the cost of care,1013 evaluate the effects of provider practices on the delivery of care,1417 and explore the effects of important policy changes on physician practices and patient outcomes 1823. The use of the Medicare databases as sources for epidemiologic and health outcomes research has increased substantially over time (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…If approved, CMS enters into a Data Use Agreement (DUA) with the researcher. These data have been used to describe patterns of morbidity2 and mortality3 and burden of disease,4,5 compare the effectiveness of pharmacologic therapies,6–9 examine the cost of care,1013 evaluate the effects of provider practices on the delivery of care,1417 and explore the effects of important policy changes on physician practices and patient outcomes 1823. The use of the Medicare databases as sources for epidemiologic and health outcomes research has increased substantially over time (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the U.S. Food and Drug Administration (FDA) issued safety alerts in 2006 and required pharmaceutical companies to add safety warnings to ESA labels (i.e., "black box" warnings) in 2007-2008. (Appendix A provides a timeline of the events involved in the development of safety concerns around ESAs). (Arneson et al, 2012;Henry et al, 2012;Hess, Nordyke, Hill, & Hulnick, 2010;Yu, Shord, & Cuellar, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Community practice-based studies using medical records data have reported 10.9% to 32.0% prepost decline in ESA use rates (Henry et al, 2012;Hess et al, 2010). A Medicare claims-based study reported a 19.8 percentage point decline in ESA use rates (35.0% pre-NCD to 15.2% post-NCD) among solid tumor and lymphoma patients with chemotherapy-induced anemia (Arneson et al, 2012). These studies also found increased rates of blood transfusion in this patient population post NCD (Arneson et al, 2012;Henry et al, 2012;Hess et al, 2010;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Current regulations have frightened many physicians from using ESAs at all . In many cases, these restrictions resulted in the abandonment of an effective therapy, often in favor of allogeneic blood transfusions, perhaps to the detriment of the patients …”
mentioning
confidence: 99%
“…9 In many cases, these restrictions resulted in the abandonment of an effective therapy, often in favor of allogeneic blood transfusions, perhaps to the detriment of the patients. [12][13][14] The story of the rise and fall of the ESAs is not unique or unprecedented. Another example is aprotinin, a oncepromising medication used in PBM with demonstrated efficacy in reducing blood loss and transfusion rates, but later disgraced due to its troubled safety profile.…”
mentioning
confidence: 99%